Flexible intramedullary nailing versus nonoperative treatment for paediatric displaced midshaft clavicle fractures. (April 2018) - Mukhtar, I. A.; Yaghmour, K. M.; Ahmed, A. F.; Ibrahim, T.
Purpose: The treatment of displaced midshaft clavicle fractures in children remains controversial. The purpose of our study was to compare the outcome of displaced midshaft clavicle fractures in children who were managed operatively by flexible intramedullary nailing (FIN) with nonoperative treatment. Methods: A prospective review of 31 children (mean age 10.5 years) with displaced midshaft clavicle fractures treated either by FIN or nonoperatively and with at least a six-month follow-up was undertaken. In all, 24 children underwent FIN and seven underwent nonoperative treatment. The patient outcomes included the Constant-Murley score, Customer Satisfaction Questionnaire (CSQ-8), numeric pain rating scale, time to union and time to return to activity. Surgical complications were recorded. Results: The two groups were comparable with regards to age, gender and mechanism of injury. At six months of follow-up, the Constant-Murley (97.8 versus 94.7, p < 0.001) and CSQ-8 (29.1 versus 19.1, p < 0.001) scores were higher in the FIN group. Time to union and return to activity were significantly shorter in the FIN group (7.3 and 9.2 weeks versus 10.4 and 16.6 weeks respectively, p < 0.01). The only surgical complication was a FIN exchange for skin irritation due to nail prominence. Conclusion: FIN is a minimally invasive procedure for children with displaced midshaft clavicle fractures associated with shorter time to union, quicker return to activity and higher Constant-Murley and CSQ-8 scores when compared with nonoperative treatment. However, the difference in Constant-Murley scores was not clinically significant. Furthermore, the advantages of FIN are at the expense of an increased complication rate of 12.5% (upper 95% confidence interval 33.3%). Level of Evidence: Therapeutic, II